2007
DOI: 10.1177/0091270007307572
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Lamivudine, Zidovudine, and Nevirapine Administered as a Fixed‐Dose Combination Formulation Versus Coadministration of the Individual Products

Abstract: The pharmacokinetics of 150 mg lamivudine, 300 mg zidovudine, and 200 mg nevirapine were assessed following single oral administration of a fixed-dose combination tablet and coadministration of the separate innovator products in healthy male subjects (n = 64) under fasting conditions in an open-label, randomized, 2-way crossover study. Multiple blood samples were collected up to 72 hours and plasma concentrations of antiretrovirals were assayed using liquid chromatography/tandem mass spectrometry methods. Phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
5
17
1
Order By: Relevance
“…Interestingly, the effect of nevirapine induction on CYP2B6 activity leads to an increased concentration of 3-hydroxynevirapine and a lower concentration of the 2-hydroxynevirapine metabolite formed through the CYP3A pathway. The pharmacokinetic characteristics of parent nevirapine in the present study agree with those of previous studies conducted in patients or volunteers after a single dose or at steady state, a finding which clearly demonstrates the autoinducing properties of nevirapine (10,(19)(20)(21)(22)(23)(24)(25)(26)(27). Indeed, the two populations studied herein differ by their ethnicity, demographics, and HIV infection status; the CYP2B6 *1*6 genetic polymorphism frequency is very close, but the significant difference remains when clearances are weight normalized (0.83 ml/ min/kg versus 0.29 ml/min/kg).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the effect of nevirapine induction on CYP2B6 activity leads to an increased concentration of 3-hydroxynevirapine and a lower concentration of the 2-hydroxynevirapine metabolite formed through the CYP3A pathway. The pharmacokinetic characteristics of parent nevirapine in the present study agree with those of previous studies conducted in patients or volunteers after a single dose or at steady state, a finding which clearly demonstrates the autoinducing properties of nevirapine (10,(19)(20)(21)(22)(23)(24)(25)(26)(27). Indeed, the two populations studied herein differ by their ethnicity, demographics, and HIV infection status; the CYP2B6 *1*6 genetic polymorphism frequency is very close, but the significant difference remains when clearances are weight normalized (0.83 ml/ min/kg versus 0.29 ml/min/kg).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, Manosuthi et al (30) recently reported that interpatient variability in the efavirenz group was 2.3-fold greater than in the nevirapine group, although these patients received concomitant use of rifampin, which could alter variability. The estimation of nevirapine CL/F calculated at steady state in our population is in the range, albeit somewhat lower, of values in previous studies including different populations (2.95 to 3.35 liters/h) (11-13, 17, 33, 42, 50) and is roughly twice the apparent clearance reported after single-dose administration (21,31), which clearly shows the importance of the autoinducing effect on either first-pass effect and bioavailability or total clearance. The 95% confidence interval for the apparent volume of distribution is large (111 to 446 liter), as the estimation error of this parameter is high.…”
Section: Discussioncontrasting
confidence: 54%
“…The 95% confidence interval for the apparent volume of distribution is large (111 to 446 liter), as the estimation error of this parameter is high. Therefore, comparison with other studies reporting somewhat lower values is difficult (21,31). Interpatient variability in V/F and k a could also not be estimated.…”
Section: Discussionmentioning
confidence: 91%
“…The total number of PBMCs is the sum of the CD4 + and CD4 − cells. The former are available for the different studies (Barry et al, 1996;Aweeka et al, 2007;Flynn et al, 2007;Marier et al, 2007), while the latter has been set to 800 [10 6 cells/L] (based on an average total PBMC count of 1600 in healthy subjects, with a CD4 − fraction of ∼ 50%) (Bisset et al, 2004).…”
Section: Detailed Physiologically Based Pharmacokinetic Model Of Zidomentioning
confidence: 99%